PKM Production Improvement Rabbit Farmer Group in the Bedugul Tourism Area, Tabanan-Bali - Wirajaya, Anak Agung Ngurah Mayun; Yuliartini, Made Sri; Sanjaya, I Gusti Agus Maha Putra; Udayana, I Gusti Bagus; Mahardika, Ida Bagus Komang; Dusak, Putu Gede Janardhana; Putra, I Ketut Suwarmadi; Mertayasa, Komang Gede (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bedugul tourist attractions with the lake and the attractive Beratan Temple, the